Groundwork for a New Theory of Democracy and Protectionism - Mendonça, Pedro (2021)
Recent protectionist tendencies in affluent democracies challenge the mainstream consensus of democracy and free trade as a virtuous relationship. Attempts to pin this protectionism on the undemocratic nature of accompanying populism cannot really be backed by existing theory. This article argues there is a theoretical void concerning the nexus of political regimes and international trade that is clearly exposed by ongoing populistic protectionism. The central theory on the political economy of democracy and trade liberalization, here dubbed the Stolper-Samuelson-Meltzer-Richards theory (SSMR) is critically examined. The SSMR has been used to explain both causal directions of the democracy/trade nexus. Each direction is explained by its own version of the SSMR, and these versions are mutually exclusive. An extensive review of empirical studies is presented to show that the predictions of the SSMR are met with a mix of support and rejection. The paper then explores the weaknesses of the SSMR and how it can be refashioned to accommodate an endogenous relationship between regime change and trade liberalization. A coupling of theory inspired by Stolper and Samuelson with the selectorate theory (Mesquita, 2003) is proposed as an avenue of future theory-building that mitigates the weaknesses of the SSMR and potentially explains populist protectionism.